Exploring maternal-fetal interface with in vitro placental and trophoblastic models - Liu, Xinlu; Wang, Gang; Huang, Haiqin; Lv, Xin; Si, Yanru; Bai, Lixia; Wang, Guohui; Li, Qinghua; Yang, Weiwei (Frontiers in Cell and Developmental Biology, 2023)
The placenta, being a temporary organ, plays a crucial role in facilitating the exchange of nutrients and gases between the mother and the fetus during pregnancy. Any abnormalities in the development of this vital organ not only lead to various pregnancy-related disorders that can result in fetal injury or death, but also have long-term effects on maternal health. In vitro models have been employed to study the physiological features and molecular regulatory mechanisms of placental development, aiming to gain a detailed understanding of the pathogenesis of pregnancy-related diseases. Among these models, trophoblast stem cell culture and organoids show great promise. In this review, we provide a comprehensive overview of the current mature trophoblast stem cell models and emerging organoid models, while also discussing other models in a systematic manner. We believe that this knowledge will be valuable in guiding further exploration of the complex maternal-fetal interface.